Redefining endogenous Bugis Limas houses in Johor - religious aspects / Liyana Mahfuzah Mohd For ... [et al.] - Mohd For, Liyana Mahfuzah; Salam, Hailane; Azmin, Aida Kesuma; Mohamed Rafie, Muhammad Firdaus; Ibrahim, Azri; Mohd Idris, Kamal; Mustapha Kamal, Fatmah Adhilah (UiTM Press, 2024)
This study highlights the neglect of intrinsic architectural values crucial to defining the identity of places within contemporary Malaysian communities and practices. Often overlooked, these values, termed ‘Endogenous Architecture’, stem from the traditional wisdom of culturally advanced societies and shape the physical appearance of traditional dwellings. The thesis posits that these values can redefine Malaysian architectural identity. It focuses on Johor's traditional Limas houses, heavily influenced by the Bugis ethnic migrant community from Sulawesi. Data were collected through open-ended interviews with experts and authorities and case studies in Pontian, Johor, where traditional Bugis Limas houses, known for their timeless preservation and influential endogenous attributes, were analysed. The research categorises the common endogenous denominators of these houses into cultural, religious, and behavioural aspects, with religion identified as the most dominant due to the Bugis community's strict adherence to Islamic rulings. Findings show that the implicit values of Bugis Limas houses remain relevant, as the community still adheres to these traditional principles. The study illustrates how these values can inform essential design guidelines, encouraging architects to integrate traditional Malay elements to create a meaningful Malaysian architectural identity. By incorporating these principles into their designs, architects can authentically reflect Malaysian identity in buildings, fostering a connection to cultural heritage for present and future generations.